GCMS Analysis of Bakong Gayo or Gayo Tobacco (Nicotiana tabacum L) Leaves Extract and Pharmaceutical Uses - Supiyani, Supiyani; Saisa, Saisa (Universitas Negeri Medan, 2024)
Tobacco plants are considered more destructive plants than medicinal plants. This research aims to analyze using GCMS (gas chromatography mass spectrometry) the leaves extract of Bakong Gayo or Gayo tobacco (Nicotiana tabacum L) and its pharmaceutical uses. Extraction of Gayo tobacco leaves with chloroform solvent obtained 14 phytochemical compounds in the form of alkaloids, terpenoids and fatty acids. The phytochemical compounds in Gayo tobacco can be used as antibacterial, anticancer, anti-depressant, antioxidant, sedative, aromatherapy based on references and other potential to be developed as a medicinal plant.